2023
DOI: 10.1080/20008066.2023.2172650
|View full text |Cite
|
Sign up to set email alerts
|

School connectedness and psychological resilience as mediators in the relationship between childhood abuse and suicidal ideation among Chinese adolescents

Abstract: Background: Suicide among adolescents is a huge public health concern around the world. Although childhood abuse has been established as a substantial risk factor for suicide behaviours, potential mediators in this relationship remain unclear. Objective: This study aimed to examine the mediating roles of school connectedness and psychological resilience in the association between childhood abuse and suicidal ideation among Chinese high school students. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
1
2
2
Order By: Relevance
“…A number of studies support our results. In fact, psychological resilience was a mediator (mediation = 29.6%) in the association between intra-familial childhood abuse and suicidal ideation among Chinese adolescents [58]. Similar to our findings, childhood emotional abuse had the higher mediation effect on suicidal ideation when comparing to other intra-familial ACEs in this survey [58].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…A number of studies support our results. In fact, psychological resilience was a mediator (mediation = 29.6%) in the association between intra-familial childhood abuse and suicidal ideation among Chinese adolescents [58]. Similar to our findings, childhood emotional abuse had the higher mediation effect on suicidal ideation when comparing to other intra-familial ACEs in this survey [58].…”
Section: Discussionsupporting
confidence: 87%
“…In terms of suicidal planning, our results showed higher prevalence than a Chinese study (16.3 and 12%, respectively) [56]. Alarmingly, our results showed that 10.6% of our adolescents had a suicide attempt, which is higher than previous international data that ranged between 3.3 and 7.96% [49,51,53,58,59]. Gender comparison showed a higher prevalence in females for all suicidal behavior types.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…"Psychological resilience", an individual attribute of psychological resources, is the capacity and dynamic process of maintaining health in the face of adversity or stress (Kalisch et al, 2015). Psychological resilience plays a crucial role in maintaining the mental health of university students, coping with stress, and preventing suicide risk (Yang et al, 2023; Ye et al, 2020). Compare to junior students, college students are in a transition stage from adolescence to maturity, known as emerging adulthood (EA), which is described as “full of possibilities for different development directions, with little certainty about the future, and a greater range of independent exploration of life possibilities than at any other time (Arnett, 2000).…”
Section: Introductionmentioning
confidence: 99%